The 2021 Ms 6.0 Luxian (China) Earthquake: Blind Reverse‐Fault Rupture in Deep Sedimentary Formations Likely Induced by Pressure Perturbation From Hydraulic Fracturing - Yingwen Zhao; Guoyan Jiang; Xinglin Lei; Caijun Xu; Bin Zhao; Xuejun Qiao (Geophysical Research Letters)
Abstract To resolve the occurrence mechanism of the Luxian earthquake occurred near an active hydraulic fracturing well pad on 15 September 2021, we first use seismic waveforms to invert the focal mechanism solution and centroid depth, and then utilize Sentinel‐1 Synthetic Aperture Radar images and Global Navigation Satellite System observations to determine the seismogenic fault and slip distribution. Our results show that the Luxian event ruptured a previously‐unmapped southwest‐dipping reverse fault intersecting with one horizontal well of the well pad. Major slip occurred below the shale gas bed (∼4 km deep) but above the crystalline basement (∼7 km deep). Further analyses on preseismic surface deformation initiated in the northeast of the event reveal that pore pressure near the hypocenter was increased by ∼4.5 MPa. Consequently, fracking fluid injected through the horizontal well and other wells of nearby pads likely flowed directly into the fault zones and prompted the occurrence of the Luxian earthquake.